Use Of Plants To Remediate Soil Polluted With Oil (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the present investigation the growing and development ability of various annual and perennial plants to grow on model peat substrate artificially polluted with oil products in the range of concentrations from 1 to 5% was evaluated. The highest tolerance towards peat contamination by oil products has been demonstrated by three annual crops (maize, oat and lupine). These plants were tested for phytoremediation of polluted black soil from the area of oil refinery plant (Mazeikiai, Lithuania), which was treated by association of oil oxidizing bacteria up to residual concentration of the oil products of 4.5 %. The maize plants revealed the highest remediation ability: oil content in the soil decreased by ~ 1.5 times in one month plant vegetation.